Distance and intensity profiles in division i women's soccer matches across a competitive season - de Oliveira Junior, M. N. S.; Veneroso, C. E.; Passos Ramos, G.; Johnson, K. E.; Guilkey, J. P.; da Costa Sena, A. F.; Cabido, C. E. T.; Cholewa, J. M. (Sports, 2021)
Women`s participation in soccer has increased rapidly. The purpose of this study was to evaluate the physiological demands imposed on women`s NCAA Division I soccer players across a season according to speed, total distance traveled, and numbers of sprints measured via GPS (Polar Team Pro®). Eighteen athletes (19.2 ± 1.1 years, 50.5 ± 6.5 mL/kg/min and 23.4 ± 3.6% fat) participated in this study. The analysis was obtained through 13 official matches. Speed zones were defined as Zone 1 (1.0 to 5.99 km/h), Zone 2 (6.0 to 10.99 km/h), Zone 3 (11.0 to 15.49 km/h), Zone 4 (15.5 to 19.9 km/h) and Zone 5 (sprint > 20 km/h), with Zones 4-5 considered as high intensity running. Individual differences in playing time and total distance were highly variable due to substitutions. Average distance traveled per game in quartiles was 3.9 km, 5.6 km and 7.4 km in the 25th, 50th, and 75th quartiles, respectively. Relative to playing time, players travelled an average of 113.64 ± 17.12 m/min (range: 93.7 to 143.5 m/min) and ran one sprint every 4.12 ± 2.06 min. When distance was summated and analyzed for the entire team, significant difference between halves was found for speed Zones 2, 3 and 4, with greater values found in the first half. Total distance, high intensity running and sprint distance were significantly less than previously recorded in professional players. These findings suggest that coaches should consider the unique physiological demands and recovery opportunities present in NCAA play when constructing practices and conditioning programs.